Government Supervision on Live-selling by Producers in TikTok Live Towards the Survival of MSMEs in Economic Globalization - Imelda Patricia; Evi Kongres (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
This special issue looks at how the role of government supervise the action of live-selling using TikTok platform by producers towards the survival of Micro, Small, and Medium Enterprises (MSMEs). Which will be reviewed from the Law of Convenience, Protection and Empowerment of Cooperative and MSMEs and the Law of Business Licensing, Advertising, Guidance and Supervision of Business Actors in Electronic Transaction Systems. This research aims to find the answer to legal regulations regarding the action of live-selling using TikTok platform by producers and the legal protection for MSMEs due to the entry of producers / manufactures into the electronics market. Researchers use the type of normative juridical legal research with a conceptual and statutory approaches. By reviewing and analyzing the role of government, we will be able to answer the problems towards the survival of MSMEs in the economic globalization era. The government has a pivotal roles to support the empowerment of micro, small, and medium enterprises, as well as the electronic system business actors, and to protect consumers also encourage the development of transactions through electronic systems. The government have to pay attention to dynamic technological developments and to prevent all forms of unfair business competition practices or manipulation practices both directly and indirectly that could lead to potential monopoly business in electronic transaction systems.